2013
DOI: 10.1016/j.actbio.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioned 70S30C bioactive glass foams promote osteogenesis in vivo

Abstract: Bioactive glass scaffolds (70S30C; 70% SiO2 and 30% CaO) produced by a sol-gel foaming process are thought to be suitable matrices for bone tissue regeneration. Previous in vitro data showed bone matrix production and active remodelling in the presence of osteogenic cells. Here we report their ability to act as scaffolds for in vivo bone regeneration in a rat tibial defect model, but only when preconditioned. Pretreatment methods (dry, pre-wetted or preconditioned without blood) for the 70S30C scaffolds were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 65 publications
(92 reference statements)
5
88
0
Order By: Relevance
“…This verified that calcium in TG was depleted after immersion in pSBF, leaving a network of silica. This supports in vivo results on porous scaffolds of the same sol-gel derived bioactive glass (70 mol% SiO 2 and 30 mol% CaO), that calcium release is too rapid from that composition [28]. The in vivo results showed that, while the scaffolds were not toxic, the calcium dissolution inside the pore structure caused a pH rise that promoted bone growth around the scaffold, rather than through it.…”
Section: Resultssupporting
confidence: 76%
“…This verified that calcium in TG was depleted after immersion in pSBF, leaving a network of silica. This supports in vivo results on porous scaffolds of the same sol-gel derived bioactive glass (70 mol% SiO 2 and 30 mol% CaO), that calcium release is too rapid from that composition [28]. The in vivo results showed that, while the scaffolds were not toxic, the calcium dissolution inside the pore structure caused a pH rise that promoted bone growth around the scaffold, rather than through it.…”
Section: Resultssupporting
confidence: 76%
“…Those materials are able to stimulate osteogenesis via both their dissolution and degradation products. Soluble silica ions activate and stimulate osteoprogenitor cells at the implant site, promoting bone tissue growth [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The objectives of this paper were to: i) Revisit the original Stöber process to provide a comprehensive understanding of how to reliably control particle size, whilst maintaining monodispersed particles; ii) Investigate the subsequent incorporation of calcium with complete quantitative characterisation of the nanoparticles to prove the incorporation of calcium, with the 70S30C composition (70 mol% SiO2, 30 mol% CaO) [32][33][34] as the target value; iii) Assess the dissolution of the particles in artificial lysosomal fluid (ALF) and Simulated Body Fluid (SBF) to determine how they might degrade in the body.…”
Section: Introductionmentioning
confidence: 99%